Pengaruh Edukasi Pada Ibu Hamil Anemia Melalui WAG (Whatsapp Group) Terhadap Peningkatan Kadar Hemoglobin - Sang Putri; Irmayani Irmayani; Suwanti Suwanti (Poltekkes Kemenkes Mataram, 2022)
Anemia is one of the most common health problems during pregnancy, especially in developing countries. Untreated anemia can lead to significant adverse health consequences for both mother and baby including death of both mother and baby. Health education and counseling during pregnancy are important strategies in the management of anemia. One strategy that can be used during the Covid-19 pandemic is online Health Education through the Whatsapp Group application for pregnant women who experience anemia. The purpose of this study was to determine the effect of pregnant women's education through WAG (Whatsapp Group) on increasing Hb levels in the Ampenan Health Center Work Area 2021. This research method used a Quasi Experiment with One Group Pre Test and Post Test design. The population in this study were pregnant women with anemia in the Ampenan Health Center Work Area. The sampling technique used non-probability sampling, namely purposive sampling with a sample of 30 pregnant women with anemia. Data analysis using Friedman test and Post Hoc analysis with Wilcoxon test. The results showed that there was an effect of education through the Group on the increase in Hb levels of pregnant women (p value =0,000) and significant differences in Hb levels on two measurement evaluations (p value=0,000). It is recommended to use online class media for pregnant women through WAG as an alternative media for health education or provide reinforcement after visits from health facilities.